Penegakan Hukum Pidana terhadap Pelaku Tindak Pidana Penyebaran Data Pribadi (Doxing) di Media Sosial (Studi Di Kepolisian Daerah Sumatera Utara) - Irfandi, Mhd Tree Irfandi; Munthe, Riswan; Lubis, Aldi Subhan (JUNCTO: Jurnal Ilmiah Hukum, 2023)
Personal Data Include d in the Scope of Cyber Law is the law that regulates digital matters, privacy and information security and crimes related to the definition of personal data are not found in laws and regulations. The research objective in this thesis is how the law is regulated. ITE electronic information and transactions against perpetrators of criminal acts of distributing personal data (doxing) on social media as an effort to protect personal rights and how criminal sanctions are against perpetrators of criminal acts of distributing personal data on social media. Using Empirical Normative Legal Research Methods Is an Understanding of Law in the Meaning of Norms and Implementation of Legal Rules in real behavior and is evidence of whether citizens have behaved in accordance with legal provisions or not. The results of the study show that the perpetrators of the crime of spreading personal data on social media are found in law number 19 of 2016 concerning electronic information and transactions and law number 27 of 2022 concerning personal data protection and threats of sanctions against perpetrators of distributing personal data are regulated in Article 67 with a sentence of four years in prison.